THE MAIN CHARACTERISTICS OF THE DEVELOPMENT OF THE LIVESTOCK NETWORK IN UZBEKISTAN (Proceedings of International Educators Conference, 2024)
The article describes the features of development of cattle breeding, which is considered the main branch of agricultural production, territorial aspects, and the measures implemented in order to satisfy the needs of the population.